2020
DOI: 10.3390/ijerph18010155
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Identify Predictors of Potentially Inappropriate Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) Use in Older Adults with Osteoarthritis

Abstract: Evidence from some studies suggest that osteoarthritis (OA) patients are often prescribed non-steroidal anti-inflammatory drugs (NSAIDs) that are not in accordance with their cardiovascular (CV) or gastrointestinal (GI) risk profiles. However, no such study has been carried out in the United States. Therefore, we sought to examine the prevalence and predictors of potentially inappropriate NSAIDs use in older adults (age > 65) with OA using machine learning with real-world data from Optum De-identified Clinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The OARSI guidelines fully supported this indication [ 4 ]. It must be remembered that continuous NSAID use should be never ‘chronic’, a recommendation that is supported by safety concerns, a lack of long-term trials, and the recent finding that a large number of patients are taking NSAIDs inappropriately (including those with multimorbidity) [ 21 ]. Finally, despite no significant difference in efficacy between cyclooxygenase-2 (COX-2) selective, partially selective, or non-selective NSAIDs, the most recent literature regarding NSAIDs suggests that celecoxib may reduce pain more effectively than other medications in knee OA [ 22 ], with the potential added benefit of the suppression of inflammation [ 23 , 24 ].…”
Section: Safety and Efficacy Of Paracetamol And Non-steroidal Anti-in...mentioning
confidence: 99%
“…The OARSI guidelines fully supported this indication [ 4 ]. It must be remembered that continuous NSAID use should be never ‘chronic’, a recommendation that is supported by safety concerns, a lack of long-term trials, and the recent finding that a large number of patients are taking NSAIDs inappropriately (including those with multimorbidity) [ 21 ]. Finally, despite no significant difference in efficacy between cyclooxygenase-2 (COX-2) selective, partially selective, or non-selective NSAIDs, the most recent literature regarding NSAIDs suggests that celecoxib may reduce pain more effectively than other medications in knee OA [ 22 ], with the potential added benefit of the suppression of inflammation [ 23 , 24 ].…”
Section: Safety and Efficacy Of Paracetamol And Non-steroidal Anti-in...mentioning
confidence: 99%
“…Many authors have confirmed the effectiveness and good tolerability of the use of Traumeel S ointment in their works [ 16 , 23 , 24 ]. Non-steroidal anti-inflammatory drugs (NSAIDs) have become the primary drugs used to treat pain, trauma and inflammation [ 25 , 26 ]. A therapeutic alternative to NSAIDs in the treatment of OA is Traumeel S. Non-steroidal anti-inflammatory drugs (NSAIDs) and Traumeel S ointment have shown comparable analgesic efficacy in patients with OA [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, Patel et al (2020) built prediction models using cross-validated logistic regression (CVLR) and XGBoost to screen predictors of potentially inappropriate osteoarthritis in the elderly with NSAIDs. The machine learning algorithms used in this study included two machine learning algorithms used by Patel et al (2020) . Compared to this study, Patel et al (2020) reported a better predictive performance with an AUC of 0.8341 and an accuracy of 0.7160.…”
Section: Discussionmentioning
confidence: 99%
“…The machine learning algorithms used in this study included two machine learning algorithms used by Patel et al (2020) . Compared to this study, Patel et al (2020) reported a better predictive performance with an AUC of 0.8341 and an accuracy of 0.7160. However, Patel’s study did not perform external validation and had poor generalization ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation